Perubahan Kadar Komponen Kimia pada Tiga Jenis Bambu Akibat Proses Steam dan Pembilasan (Chemical Components Changed in Three Bamboo Species Treated by Steaming and Washing Processes) - Murda, Rio A; Nawawi, Deded S; Maulana, Sena; Maulana, Muhammad I; Park, Se-Hwi; Febrianto, Fauzi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Bamboo has good prospects for composite raw materials such as for Oriented Strand Board (OSB) product. Previous research has shown that steam and rinsing with water and 1% NaOH solution treatments of strand improved the properties of OSB, which might be caused by changing in the chemical components content of bamboo. This study aimed to determine the chemical components content change of sembilang bamboo (Dendrocalamus giganteus Munro), black bamboo (Gigantochloa nigrocillata Kurz.), and tali bamboo (G. apus (Bl.ex Schult.f.)) due to steam and rinsing treatment. The chemical components of bamboo were analyzed referring to the Technical Association of the Pulp and Paper Industry standards (TAPPI). The results showed that the most significant changes in the chemical components content of bamboo occured for holocellulose, hemicellulose, extractive contents, and pH values. The decreasing of hemicellulose, extractive contents, and increasing pH values due to the steam and 1% NaOH rinsing treatment may improve the adhesion quality of OSB.Keywords: bamboo, chemical components, steam modification, strand,